Sintesis Hidroksiapatit Dari Precipitated Calcium Carbonate (PCC) Terumbu Karang Melalui Proses Presipitasi Dengan Variasi Temperatur Dan Waktu Ageing - Kayabi, Ulhunk Aulia; Yelmida, Yelmida; Evelyn, Evelyn (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Hydroxyapatite is a bioceramics that is widely used as a bone and tooth grafting material, catalyst and adsorbent. Hydroxyapatite is a calcium phosphate compound that can be synthesized from natural ingredients with high calcium content such as coral reefs. Coral reef is a marine biota that has a CaCO3 content of 98.8%. This study aims to synthesize hydroxyapatite through the formation of Precipitated Calcium Carbonate (PCC) from coral reefs. The research procedure begins with the process of calcination of coral reefs to form CaO which is then made into PCC with carbonation methods. PCC as a source of calcium is synthesized into hydroxyapatite using precipitation processes with variations in temperature (30°C, 50°C and 70°C) and aging time (7 hours, 14 hours and 21 hours). Synthesized hydroxyapatite was analyzed by X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). The results of XRD analysis showed the formation of hydroxyapatite compounds from 2 sudut angles in accordance with the data (ICDD 01-074-0565). Hydroxyapatite which was synthesized at a temperature of 50⁰C and aging time gave the best results with a monoclinic crystal structure, a degree of crystallinity of 96.0772% and a crystal size of 20.1846 nm. The resulting hydroxyapatite can be developed as bone implant material, catalyst or adsorbent. Keywords: degree of crystallinity, PCC, temperature, ageing time